EFEITO DE TiO2 K2O , E Na2 FASE VÍTREA E NAS PROPRIEDADES DE PORCELANAS TRIAXIAIS. - Przybysz, Aldo (2011)
Porcelains are manufactured from natural raw material, in which are inclined the presence of diverse impurities. The presence of impurity can modify significantly the various characteristics of the porcelain, mainly the mechanical characteristics. Then, the understanding about the mechanism of actuation of these impurities is fundamentally important to reach the desired characteristics. In this dissertation, it was studied the effects of the addition of oxide generators additives on the microstructural development and on the properties of aluminous porcelain, siliceous and aluminous-siliceous, aiming to understand the actuation mechanism of these additives and what is their influence with the variation of ceramic mass composition. It had been chosen three types of porcelain: Porcelain of Alumina-Feldspar-Kaolin system, Silica-Feldspar-Kaolin and Alumina-Silica-Feldspar-Kaolin. In each composition it was added the additives, which were mixed wet in balls mill, and dry in stove. The resulting powders from these mixtures were pressed and sintered. The sintered porcelains were characterized by apparent density measurement, water absorption, linear contraction, porosity percentage, X-ray diffraction, electronic microscopy scan, EDS microanalyses and rupture module by three points flexion. In the aluminous, siliceous and the aluminous-siliceous porcelains compositions, the presence of additives reduced the values of the modules of rupture, nevertheless for the major of the samples added to these additives, the sintering temperature was reduced. It was verified that in every composition and with every additive used, actuate directly on the formation of the liquid stage, and it is this stage that during the sintering, modifies the other present stage and then, modify the microstructure and consequently the mechanical characteristics of the porcelain.